Azadirachtin Affects the Growth of Spodoptera litura Fabricius by Inducing Apoptosis in Larval Midgut - Shu, Benshui; Zhang, Jingjing; Cui, Gaofeng; Sun, Ranran; Yi, Xin; Zhong, Guohua (Frontiers in Physiology, 2018)
Azadirachtin, the environmentally friendly botanical pesticide, has been used in integrated pest management as an antifeedant and pest growth regulator for multiple decades. Azadirachtin has shown strong biological activity against Spodoptera litura, but the mechanism of toxicity is not fully understood. The present study shows that azadirachtin inhibits the growth of S. litura larvae. This growth inhibition is mediated by inhibiting the midgut size and structure, a major organ for food digestion and nutritional absorption. Digital gene expression analysis suggested that midgut epithelial cells regulated the transcriptional level of multiple genes involved in the mitogen-activated protein kinase (MAPK) and calcium apoptotic signaling pathways. These expression patterns were verified by quantitative real time (qRT)-PCR. Azadirachtin inhibits midgut development via induction of apoptosis in midgut cells, which was confirmed by increased terminal deoxynucleotidyl transferase biotin-dUTP nick end labeling (TUNEL) staining, increased gene and protein expression of apoptosis-related genes (including inhibitor of apoptosis-binding motif 1 [IBM1] and caspase family members), and the release of cytochrome c from the mitochondria to the cytoplasm. These results demonstrate that azadirachtin induces structural alteration in the S. litura larval midgut by activation of apoptosis. This alteration of the midgut may affect the digestion and absorption of nutrients by midgut cells, inhibiting S. litura larval growth.